EFFORTS TO IMPROVE STUDENTS 'RESPONSIBILITIES IN MATHEMATICS LEARNING USING THE JIGSAW TYPE COOPERATIVE LEARNING MODEL IN CLASS VII B STUDENTS OF SMP NEGERI 13 YOGYAKARTA - Erma Dewi Prastiya; Uswatun Khasanah (Universitas Ahmad Dahlan, 2017)
Teacher-centered learning caused the students are not serious, enthusiastic, and confident in their own ability so that students are not so responsible in following the learning of Mathematics for the students of class VII B SMP Negeri 13 Yogyakarta. The use of the Jigsaw type cooperative learning model in Mathematics learning is expected to improve student responsibility better than usual. This study aims to improve students responsibility in learning mathematics the students of class VII B SMP Negeri 13 Yogyakarta in the odd semester Academic Year 2016/2017 by using the Jigsaw type cooperative learning model. This research included in Classroom Action Research. The subjects in this study were the students of class VII B SMP Negeri 13 Yogyakarta in the odd semester, which amounted to 34 students consisting of 18 female students and 16 students of the male. Data collection techniques through observation, interviews, and triangulation. The instruments used in this data collection are observation sheets and interview guides. The data analysis used is quantitative and qualitative analysis. The criterion of success in this study is the responsibility of students in involving the learning process increases if the student’s responsibility reaches at least 61%. The result of the research shows that learning with the Jigsaw type cooperative learning model on VII B students of SMP Negeri 13 Yogyakarta in the academic year of 2016/2017 increase the student’s responsibility. It is proven by the result of student responsibility observation every cycle has increased, that is the percentage of success of student responsibility research in cycle I equal to 44,85 % (Enough), and in cycle II increase to 66,30% (Good).